A comprehensive association analysis confirms ZMIZ1 to be a susceptibility gene for vitiligo in Chinese population. Issue 5 (25th March 2014) - Sun, Yonghu; Zuo, Xianbo; Zheng, Xiaodong; Zhou, Fusheng; Liang, Bo; Liu, Hong; Chang, Ruixue; Gao, Jinping; Sheng, Yujun; Cui, Hongzhou; Wang, Wenjun; Andiappan, Anand Kumar; et al.
Abstract : Background: ZMIZ1 has been shown to be associated with multiple autoimmune diseases and play a role in the development of melanocyte. The association of ZMIZ1 with vitiligo was also suggested, but the evidence did not reach genome-wide significance and has not been confirmed by independent studies. Methods: A fine mapping analysis of the ZMIZ1 locus was carried out in the dataset of 1117 vitiligo patients and 3437 controls through deep imputation. Ten suggestive SNPs were then analysed in an independent validation cohort of 7458 cases and 7542 controls. SNPs within ZMIZ1 locus were functionally annotated using the ENCODE and RegulomeDB databases and published eQTL dataset of primary immune cells. Results: A genome-wide significant association was discovered at rs1408944 (ORcombined =1.18, pcombined =1.38E-09) that locates at a DNAse hypersensitivity site and within a Myb_1 motif carried by the binding sites of six overlapping transcription factors (TFs) within the region. Gene Relationships Across Implicated Loci (GRAIL) analysis revealed biological connectivity between ZMIZ1 and previously discovered susceptibility loci for vitiligo as well as the six TFs. Conclusions: Our study has confirmed ZMIZ1 as a novel susceptibility locus for vitiligo and further suggested rs1408944 to be the putative causal variant that potentially interrupts TF binding and thus the transcriptional regulation of ZMIZ1 .